HOW EMPLOYEE BENEFITS AND WORK DISCIPLINE AFFECT EMPLOYEE PERFORMANCES IN THE BONE BOLANGO DEPARTMENT OF COMMUNITY AND VILLAGE EMPOWERMENT (DPMD) - Salim, Yayuk Juliarti; Abdussamad, Zuchri; Tui, Fenti Prihatini (Public Policy Journal, 2021)
This research gives the analysis of how employee benefits and work discipline affect employee performances in the Bone Bolango Department of Community and Village Empowerment (DPMD), either in partial or simultaneous. It used a quantitative approach and an ex post facto research method. The research design was causality. The research population was made up of 48 people. Using a saturation sampling method, we acquired 48 research samples. Data collection techniques were questionnaire, observation, and documentation. The data analysis technique used was double regression. Findings present that (1) Employee benefits (TPP) had a positive and significant impact on employee performances in the Bone Bolango Department of Community and Village Empowerment (DPMD) at a coefficient of determinatioan of 14.60%, (2) Work discipline had a positive and significant impact on employee performances in the Bone Bolango Department of Community and Village Empowerment (DPMD) at a coefficient of determination of 61.20%, (3) Employee benefits (TPP) and work discipline simultaneously had a positive and significant impact on employee performances in the Bone Bolango Department of Community and Village Empowerment (DPMD) at a coefficient of determination of 75.20%, while the rest, 24.80%, was elucidated by other variables unexplained in this research, such as communication, organizational culture, employee competency, work commitment, and information and communication supports. Optimizing both employee benefits and work discipline is thus foreseeable to elevate employee performances in the Bone Bolango Department of Community and Village Empowerment (DPMD).